Efektivitas Ekstrak Mimosa Pudica Terhadap Penurunan Jumlah Blastocystis sp. Pada Tikus Wistar Model Diare Akut - Yanti Rahayu; Nuzulia Irawati (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Blastocystis sp. infection is a prevalent cause of gastrointestinal disorders, contributing to acute diarrhea through inflammatory mechanisms and intestinal mucosal damage. Although metronidazole remains the standard antiparasitic therapy, its use is constrained by side effects and variable efficacy, underscoring the need for safer and more effective alternative treatments derived from natural sources. Mimosa pudica is known to contain bioactive compounds, including flavonoids, tannins, saponins, and alkaloids, which exhibit antiparasitic and anti-inflammatory activities. Objective: This study aims to evaluate the effect of Mimosa pudica leaf extract on reducing parasite numbers in a Wistar rat model of acute diarrhea induced by Blastocystis sp. Methods: Leaf extracts were prepared using ethanol as a solvent and were characterized using Fourier Transform Infrared (FTIR) spectroscopy and phytochemical screening. An in vivo test was conducted in 40 male Wistar rats, divided into six groups: a negative control, a positive control, two metronidazole-treated groups (9 and 13.9 mg), and two extract-treated groups (40 and 80 mg). The primary parameters observed included parasite count in fecal samples, stool consistency, and motor activity. Results: Phytochemical analysis confirmed the presence of flavonoids, tannins, saponins, and alkaloids in the extract. FTIR spectra revealed functional groups such as hydroxyl (–OH), carbonyl (C=O), and aliphatic groups (C–H), which are characteristic of bioactive polyphenolic compounds. In vivo results demonstrated that Mimosa pudica extract significantly reduced Blastocystis sp. burden and improved clinical conditions, including stool consistency, in a dose-dependent manner. The 80 mg dose exhibited the highest efficacy, with 80% of samples becoming parasite-free by day 7 of treatment. Conclusion: The findings indicate that Mimosa pudica extract exhibits significant antiparasitic activity against Blastocystis sp. and shows potential as a therapeutic agent for treating protozoan infections, particularly in the context of acute diarrhea. Further research is warranted to elucidate the precise molecular mechanisms and to evaluate its safety and clinical applicability.